EVALUASI PERTUNJUKAN TEATER TERHADAP RETENSI PENGETAHUAN DAN PENURUNAN STIGMA HIV/AIDS PADA WARGABINAAN DI LAPAS NARKOTIKA BANCEUY BANDUNG - , Nisaa Nur Alam, Dra. Retna Siwi Padmawati, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: The high prevalence of HIV has in line with the high stigma of HIV/AIDS in Banceuy Prison. Stigma of HIV/AIDS will aggravate PLWHAâs (people living with HIV/AIDS) health and obstruct prevention of HIV/AIDS programs. Theatre as health promotion program is one of the efforts to reduce stigma of HIV/AID as well as to improve inmates knowledge of HIV/AIDS. The theatre has been evaluated qualitatively by previous research. Hence, to obtain optimal findings, the authors conducted quantitative study in short-term and long-term evaluations. Objectives: This study was aimed to determine the effectiveness of theatrical performance in the improvement of knowledge of HIV/AIDS, providing retention of knowledge, and reducing the stigma of HIV/AIDS. Methods: The study has used mixed methods design, quasi-experiment by pretest and posttest with control group design by self-administered questionnaires and in-depth interviews. The quantitative study used 300 sample in short-term evaluation, it decreased to 144 sample in long-term evaluation. Data analysis had used independent t-test, paired t-test, chisquare test, stratification, and logistic regression. The qualitative study used 15 sample and thematic analysis for data analysis. Results: In short-term evaluation, in the treatment group, the knowledge scores increased significantly (p=0.005), and the stigma scores has no different between pretest and posttest. However, the stigma scores decreased significantly (p=0.003) in the control group. In the long-term evaluation, stigma scores increased significantly in both groups (p=0.000). Knowledge had relationship with stigma (p=0.000) with OR=4.7. In qualitative results, the theatre provides knowledge retention on certain inmates who have the same story of their life as drug user with the main actor, and stigma had contributed to reduce stigma of HIV/AIDS. Conclusion: Theatre is one of IEC programs and it could not be used as a single effort for reducing stigma of HIV/AIDS. Hence, It is recommended to provide continuous IEC and to collaborate with related networks.